Preservation and Organization of Electronic Resources for Effective Service Delivery in Federal College of Education Libraries in Northern Nigeria - Andrew , Temboge,; A. Bappah, Magaji, (Kashere Journal of Education, 2021)
The study investigated the preservation and organization of electronic resources for effective service delivery in Federal College of Education Libraries in Northern Nigeria. The objective is to examine the electronic resources preservation strategies, ICT facilities used for resources preservation, organization of electronic resources and types of electronic resources organized. The research adopted qualitative research methodology. The population of the study is the 12 college librarians and was sampled. Interview was used for data collections, data collected were analyzed using thematic analysis. The findings revealed that, the strategies applied for preservation of resources were migration and normalization. The libraries used external hard drive, drop box/cloud and institutional repository for preserving electronic resources. Majority of the libraries organize their resources. In conclusion, proper management of e-resources is a prerequisite to easy access and use of the resources to enhance research, teaching and learning. The study recommended the use of preservation strategies that can prolong the life span of the resources; organize the resources for easy retrieval; provides access to the resources remotely and lastly, the management of the colleges and their libraries should ensure that all the challenges are minimized in order to provide access for use of the resources